IoT Application in Designing Ship Trim Reading and Monitoring Tools - Zulfaidah Ariany; Fairuzabadi Fakhruddin; Suryanusaciptaning Akbar; M. Sawal Baital; Ahmad Ridho Hanifuddin (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
The shipping industry is widely adopting appropriate technologies in various areas to overcome challenges and improve efficiency. However, ship loading and unloading efficiency remains a significant concern in terms of cost and time. Monitoring the loading and unloading process relies heavily on Android-based manual input calculations, indicating the potential for technological application in the draft survey process. This research initiates the development of an Internet of Things (IoT) application to monitor trim readings during the draft survey of a ship. The planning involved initial stability calculations to add data to the IoT module planning. The resulting tool aims to improve efficiency by providing real-time trim and ship balance data during loading and unloading operations. Additionally, this research demonstrates the potential of IoT technology in optimizing shipping logistics and can be further developed with more advanced technology to advance the maritime industry.